THE INFLUENCE OF WORK MOTIVATION, CO-WORKER SUPPORT, AND RELIGIUS ON JOB SATISFACTION OF AL-ANIS KARTASURA KOPPONTREN EMPLOYEES - Akbar, Abu Bakar (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this research was to determine the effect of work motivation, co-worker support, and religiosity on job satisfaction of Koppontren Al-Anis Kartasura employees. This study uses probability sampling and 30 respondents who are employees of Koppontren Al-Anis Kartasura. This research uses quantitative methods. The population in this study was all employees of Koppontren Al-Anis Kartasura, totaling 30 people. The sampling technique is the saturated sampling technique, which is a sample determination technique where all members of the population are sampled, so that the sample for this research consists of 30 people as respondents. The results of this research indicate that partially work motivation has a significant positive effect on job satisfaction based on the ttest (3,036) > ttable (1,705). Coworkers support has a significant positive effect on job satisfaction based on the ttest (2.067) > ttable (1.705). Religiosity has a significant positive effect on job satisfaction based on the ttest (2.353) > ttable (1.705). Work motivation, co-worker support, and religiosity have a significant positive effect on job satisfaction simultaneously. Work motivation as the most dominant independent variable affects job satisfaction as the dependent variable.